2014
DOI: 10.1111/ped.12379
|View full text |Cite
|
Sign up to set email alerts
|

Insulin glargine in pediatric patients with type 1 diabetes in Japan

Abstract: BackgroundWe evaluated the safety and effectiveness of insulin glargine in Japanese pediatric patients with type 1 diabetes in clinical settings based on post-marketing surveillance data.MethodsClinical data were collected from Japanese pediatric patients with type 1 diabetes for 24 weeks after initiation of glargine treatment. Baseline characteristics, hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), previous/concomitant medication, height, bodyweight, and adverse events were analyzed.ResultsOne-hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Insulin glargine (IGlar) has long been widely used as the main form of La, and reportedly lasts for up to 24 hours, though a waning effect can be seen at approximately 20 hours after the injection [9]. Approximately 70-80% of patients using IGlar give themselves a once-daily injection, whereas others require twice-daily injections to cover their 24-hour basal insulin supplementation [8][9][10][11]. Patients requiring twice-daily injections of basal insulin tend to need a higher dose of insulin to attain optimal glycemic targets, and experience more frequent episodes of hypoglycemia [8,10].…”
Section: Methodsmentioning
confidence: 99%
“…Insulin glargine (IGlar) has long been widely used as the main form of La, and reportedly lasts for up to 24 hours, though a waning effect can be seen at approximately 20 hours after the injection [9]. Approximately 70-80% of patients using IGlar give themselves a once-daily injection, whereas others require twice-daily injections to cover their 24-hour basal insulin supplementation [8][9][10][11]. Patients requiring twice-daily injections of basal insulin tend to need a higher dose of insulin to attain optimal glycemic targets, and experience more frequent episodes of hypoglycemia [8,10].…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have indicated that most patients using insulin glargine (IGlar) must administer more than twice-daily injections to cover their 24-hour basal insulin supplementation [6][7][8]. Insulin degludec (IDeg) is an ultra-La recently developed by Nordisk (Bagsvaerd, Denmark) that constitutes soluble multihexamers after subcutaneous injection; these molecules slowly dissociate and allow a slow and stable release of monomers into the circulation, and thus extending the action of basal insulin formula to more than 40 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 70-80% of patients using IGlar need a once-daily injection, whereas others require twice-daily injections to cover their 24 h basal insulin supplementation. These latter patients were demonstrated to need a higher dose of insulin to attain optimal glycemic targets and to experience more frequent episodes of hypoglycemia ( 13 ).…”
Section: Introductionmentioning
confidence: 99%